THE EFFECT OF MALE EXPECTED YEARS OF SCHOOLING ON THE NUMBER OF POOR PEOPLE IN INDONESIA - Handayani, Sopiah; Efendi, Achmad; Anitra, Vera (INSTITUT TEKNOLOGI DAN BISNIS PGRI DEWANTARA JOMBANG, 2026)
Poverty is a development issue closely related to the quality of human resources, particularly education. This study aims to analyze the effect of male Expected Years of Schooling (AHLS) on the number of poor people in Indonesia. This study uses a quantitative approach with secondary time series data for the period 2014-2024 sourced from the Badan Pusat Statistik (BPS). The population and sample of this study are all national data on male AHLS and the number of poor people during the observation period. The analytical method used is simple linear regression with data transformed into natural logarithms and processed using SPSS software, preceded by a classical assumption test. The results show that AHLS has a negative and significant effect on the number of poor people with a regression coefficient of -2.063 and a significance level of 0.006. The Adjusted R Square value of 0.546 indicates that 54.6 percent of the variation in the number of poor people can be explained by male AHLS. This finding suggests that increasing male education plays a significant role in poverty alleviation efforts through improving the quality of human resources in Indonesia.